Pengajian Tinggi: Pendemokrasian, Pengkomersialan dan Pengantarabangsaan, by Qasim Ahmad. Kuala Lumpur: Penerbit Universiti Malaya, 2022, 607 pp. ISBN 978-967-488-163-4. (KEMANUSIAAN The Asian Journal of Humanities, 2022)
At a glance, Pengajian Tinggi: Pendemokrasian, Pengkomersialan dan Pengantarabangsaan seems like a formidable book to take on. It is 12 chapters and is 484 pages long. Its reference section is an additional 110 pages, with thousands of materials cited throughout the book. Weaved into the writing are stories and experiences of 34 interview respondents who are household names within the Malaysian higher education community, and once held posts at the top echelons of the country’s higher education system.